Analisis Keuntungan dan Strategi Pengembangan Usaha Tani Jamur Merang (Studi Kasua Usaha Bujang Jamur di Desa Rumpet Kecamatan Krueng Barona Jaya Kabupaten Aceh Besar) - Rizki Fajri; Akhmad Baihaqi; Anwar Deli (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
Mushrooms are vegetables that are good for humans and have a fairly high nutritional value, namely potassium, protein, antioxidants, crude fiber, B vitamins, vitamin D and Beta glucan. Mushrooms can be processed as food, including mushroom soup, mushroom paste, salad, and can even be processed into a kind of crisp or chip. In 2018-2019, national mushroom production per year is in the range of 33 thousand tons, while domestic demand is estimated at 48 thousand tons. Based on this data, it means that there is still a difference of around 15 thousand tons per year that has not been able to be met from domestic production. This was a great opportunity for mushroom cultivators. This indicates that Indonesia has not been able to meet the domestic demand for mushrooms and there are many opportunities for mushroom entrepreneurs in Indonesia. There are recorded as many as 910,028 farmers throughout Aceh Province, as for Aceh Besar District, there are 61,316 farmers. There are various kinds of farming that are cultivated in Aceh Besar, one of which is mushrooms. One type of mushroom cultivated is straw mushroom (Volvariella volvaceae). Similarly to the facts above, the supply of mushrooms in Aceh is still not able to meet its high demand. One of those who have started a mushroom cultivation business in Aceh Besar is the mushroom business which is managed by Maulana. The name of this business is Bujang Jamur, located in Rumpet Village, Darussalam District, Aceh Besar Region. This study aims to analyze the advantages of the Bujang Jamur business and then determine the right development strategy by utilizing the strengths and opportunities of this business. Data analysis was carried out qualitatively and quantitatively. The data that has been obtained are analyzed using profit analysis and SWOT analysis using the IFE/EFE matrix. Data analysis begins with determining the weights of strategic factors that affect the business, then the results of the weights are analyzed using a SWOT matrix. Based on the results of the profit analysis, it was obtained that the R/C Ratio was 1.93, which means it can be said that the Merang Mushroom Business run by Bujang Mushroom is included in the profitable category. As for the SWOT analysis diagram, the Bujang Mushroom business is in quadrant I or the aggressive quadrant, which means that the strengths and opportunities available in the Bujang Mushroom business can still be utilized as much as possible so that they can take advantage of the high demand in the market.